CITRA PEREMPUAN DALAM NOVEL CERITA TENTANG RANI KARYA HERRY SANTOSO; TINJAUAN KRITIK SASTRA FEMINIS* (The Image of Women in the Novel Entitled Cerita Tentang Rani by Herry Santosa: A Feminist Literary Criticism) - Anam, Choerul (Balai Bahasa Jawa Tengah, 2019)
This study aims to describe the image of women in Herry Santoso's novel: Cerita Tentang Rani in the perspective of feminist literary criticism. The method applied in the research is a qualitative one. The purpose of the qualitative method leads the writer being able to get to know the in-depth history of the research environment by applying descriptive research types. Feminist criticism theory of Rosemarie Putnam Tong and gender theory of Judith P. Butler were applied in this research. The results of this study prove that the image of the main character, Maharani, is a strong and tough woman. The images of the woman cover 1) the image of women in her relation with Allah Swt (God); 2) the image of women in her relation with herself; and 3) the image of women in her relationship with others. Keywords: female image, feminist literary criticism, Novel Cerita Tentang Rani.